Hubungan Indeks Massa Tubuh dengan Kejadian Diabetes Melitus Tipe 2 pada Wanita Menopause di Desa Medan Estate - Febriani Br Sinaga, Lisbeth; Simatupang, Lenny Lusia (Jurnal Pustaka Keperawatan (Pusat Akses kajian Keperawatan), 2025)
Type 2 Diabetes Mellitus is a metabolic disease caused by insulin resistance and dysfunction of pancreatic beta cells. The dominant lifestyle factors contributing to Type 2 Diabetes Mellitus are dietary patterns and physical activity. This study aimed to determine the relationship between body mass index (BMI) and the incidence of Type 2 Diabetes Mellitus among menopausal women in Medan Estate Village. This study used a cross-sectional research design. The sampling technique was total sampling, in which the entire population was included as the research sample. Data analysis was conducted using the Pearson correlation test. The research instrument used an observation sheet. The results showed that there was a relationship between body mass index and the incidence of Type 2 Diabetes Mellitus among menopausal women, with a p-value of 0.001 (p < 0.05). This indicates a significant relationship between Body Mass Index and the incidence of Type 2 Diabetes Mellitus in menopausal women. It is expected that maintaining a healthy lifestyle is important, including controlling body weight to remain within a normal or ideal range, engaging in regular physical activity, and managing dietary patterns to prevent the occurrence of Type 2 Diabetes Mellitus.